P038: A procedural skills needs assessment targeting physicians providing emergency department coverage in rural Newfoundland and Labrador. (May 2019) - Dunne, C.; Parsons, M.
Abstract : Introduction : Maintaining competence in high-acuity low-occurrence (HALO) procedures is often difficult due to their infrequent occurrence. While simulation is a valuable tool to hone skills, providing effective simulation-based education (SBE) to learners outside academic centers can be challenging. Utilizing a mobile tele-simulation unit (MTU) with expert instruction from a geographically separated mentor could prove a valuable approach to overcoming barriers in this setting. However, to maximize benefit and buy-in, the training modules developed for this unique delivery method must align with the needs of those practicing in rural settings.Objectives : - To evaluate the procedural skills training needs of emergency medicine (EM) physicians in rural Newfoundland and Labrador (NL) - To inform the development of simulation modules designed for use in a MTUMethods : A web-based needs assessment was distributed to physicians registered with the NL Medical Association, working in rural locations, and having EM listed as their primary specialty. Participants evaluated their comfort, performance frequency and desire to have further training for 12 HALO procedures. Two EM physicians selected these from a broader list of core procedural skill competencies for CCFP-EM residents at Memorial University. Participants were also able to suggest other procedures that might benefit from SBE.Results : The data collection occurred for 8 weeks with a 68% response rate (N = 22). No respondents had formal EM training outside of exposure in family medicine residency. 60% had 10+ years practicing EM. Chest tube insertion (100%), difficult intubation (92.3%) and surgical airway (92.3%) were the procedures that most respondents felt required more SBE. In practice, they most often performed bag-valve ventilation, splint application and procedural sedation (>10 per year). Additional procedures felt to require SBE were central venous line placement and trauma assessment. Opportunities to participate in SBE were limited (66.7%-less than annually). Despite this, most participants agreed SBE would be a significant benefit if accessible (93.3%). The greatest barriers to SBE included lack of equipment, rural location, and time necessary for travel to larger centres.Conclusion : The provision of medical care in rural settings can be particularly challenging when HALO procedures must be performed. Unique delivery methods of SBE targeted to the needs of rural practitioners may help bridge gaps in knowledge and technical skills.